Industrial landscapes - Garner, Keith (Longman, 1981)
Contents: Where would you establish your factory?; Factors of industrial location; The micro-scale: patterns within the city; The meso-scale: the national pattern of industry; The macro-scale: world patterns of development; Manufacturing in Australia: constancy and change...